(untitled) (Journal of the Pakistan Medical Association, 2020)
Abstract The incidence of chronic kidney disease (CKD) is rising all over the world. Developing countries like Pakistan will be most affected due to the prevalence of risk factors associated with CKD, such as diabetes, hypertension, kidney stone, and infections. Chronic kidney disease of unknown aetiology (CKDu) is an emerging CKD recently recognised in agricultural communities all around the world. CKDu is recognised, mostly in men between 20 and 50 years of age, with no symptoms, having normal or borderline elevated blood pressure with normal blood glucose levels. Their ultrasonography manifests small kidneys. Urine examinations reveal no or minimal proteinuria, few red blood cells and leukocytes. The actual prevalence in Pakistan is unknown but it is not infrequent for nephrologists and physicians to see these patients in hospitals. There is a need to look into this entity at the community level. Continuous...